Has cross-border E-Commerce export increased regional entrepreneurial activity? Evidence from 31 provinces in China - Ping, Guo; Hamzah, Hanny Zurina; Chin, Lee (Routledge, 2024)
This study aims to determine the impact of CBEC export on regional entrepreneurial activity. Based on China’s provincial panel data from 2015 to 2020, this study employed ridge regression to conduct benchmark regression, heterogeneity analysis, and moderation mechanisms analysis. As a result, a significant improvement in entrepreneurship was recorded, which was attributed to CBEC exports. These exports also had a more positive impact on regional entrepreneurial activity in regions with high levels of informatization compared to those with medium and low levels. A positive moderating effect was found from the market environment on the relationship between CBEC exports and regional entrepreneurship. Furthermore, this research proposed a more reasonable estimation method for provincial-level CBEC export data based on the seller distribution ratio, followed by a perspective on CBEC exports for the Chinese government to formulate entrepreneurship incentive policies. © 2024 Informa UK Limited, trading as Taylor & Francis Group.